Integrated in situ gas stripping–salting-out process for high-titer acetone–butanol–ethanol production from sweet sorghum bagasse - Hao Wen (Biotechnology for Biofuels, 2018)
Abstract Background The production of biobutanol from renewable biomass resources is attractive. The energy-intensive separation process and low-titer solvents production are the key constraints on the economy-feasible acetone–butanol–ethanol (ABE) production by fermentation. To decrease energy consumption and increase the solvents concentration, a novel two-stage gas stripping–salting-out system was established for effective ABE separation from the fermentation broth using sweet sorghum bagasse as feedstock. Results The ABE condensate (143.6 g/L) after gas stripping, the first-stage separation, was recovered and introduced to salting-out process as the second-stage. K4P2O7 and K2HPO4 were used, respectively. The effect of saturated salt solution temperature on final ABE concentration was also investigated. The results showed high ABE recovery (99.32%) and ABE concentration (747.58 g/L) when adding saturated K4P2O7 solution at 323.15 K and 3.0 of salting-out factor. On this condition, the energy requirement of the downstream distillation process was 3.72 MJ/kg of ABE. Conclusions High-titer cellulosic ABE production was separated from the fermentation broth by the novel two-stage gas stripping–salting-out process. The process was effective, which reduced the downstream process energy requirement significantly.